2019
DOI: 10.1002/star.201800338
|View full text |Cite
|
Sign up to set email alerts
|

Pasting and Rheological Properties of Non‐Crystalline Granular Starch

Abstract: The pasting and rheological properties of non‐crystalline granular starch (NCGS) are investigated and compared with those of partially or totally gelatinized starch. At low (65 and 70 °C) temperatures, non‐gelatinized or only slightly gelatinized starch granules with a low viscosity and high flowability are dominant in the system. At intermediate treatment temperature (75 °C), the level of starch swelling and amylose leaching can be controlled to produce NCGS and its pasting and rheological properties fall som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The crystallinity of the dough containing potato pulp was more easily disrupted by freeze‐drying compared with the wheat dough. Chen et al () also confirmed that freeze‐drying had greater effects on potato starch than wheat starch. And the short‐range ordered structure of starch was confirmed as discussed in Section 3.2.…”
Section: Resultsmentioning
confidence: 87%
“…The crystallinity of the dough containing potato pulp was more easily disrupted by freeze‐drying compared with the wheat dough. Chen et al () also confirmed that freeze‐drying had greater effects on potato starch than wheat starch. And the short‐range ordered structure of starch was confirmed as discussed in Section 3.2.…”
Section: Resultsmentioning
confidence: 87%
“…The swelling of starch is a property of amylopectin, therefore amylose acts as a diluent and inhibitory in this condition. [ 38,39 ] The degree of swelling of corn starch was lower than for other starches to the temperature of 70 °C. After this temperature the wheat starch showed the lower values of swelling, Figure , indicating a more stable structure.…”
Section: Resultsmentioning
confidence: 95%
“…Due to its linear structure, amylose ages relatively easily. Under the action of hydrogen bonds, amylose aggregates and rearranges to form a double-helix structure, making a cross-networking structure [ 4 , 5 ]. Numerous studies have focused on the regulation of starch retrogradation, and blending with non-starch polysaccharides was found to be one of the effective ways of manipulating starch properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%